Surprisingly robust violations of stochastic dominance despite splitting training: A quasi-adversarial collaboration - Edika Quispe-Torreblanca; Neil Stewart; Michael H. Birnbaum (Judgment and Decision Making)
First-order stochastic dominance is a core principle in rational decision-making. If lottery A has a higher or equal chance of winning an amount